Implementation of the Village Financial System (Siskeudes) in Managing Village Fund Allocations in Cibuntu Village, Cibitung District, Bekasi Regency - Shela Sagita; Evi Priyanti; Indra Aditya (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Currently, the implementation of village financial management in Cibuntu Village, Cibitung District, Bekasi Regency has used applications based on computerized information systems. The application is the Village Financial System (Sisekudes) application developed by the Financial and Development Supervisory Agency (BPKP) torealize clean village financial management. However, in the implementation of Siskeudes in Cibuntu village there are several problems that occur. Therefore, researchers are interested in conducting research on the implementation of Siskeudes in managing village fund allocations in Cibuntu Village, Cibitung District. The research method used is a qualitative method with a qualitative approach because researchers need to go directly to the field with the object of research so that the data collection techniques used by researchers are interviews and documentation. The results showed that the implementation of the village financial system in terms of policy content had been implemented well, but there were still some obstacles that occurred, such as the internet network in Cibuntu Village which was less stable which resulted in the Siskeudes application being unable to be used. In order for the implementation of siskeudes to run well, the government must collaborate with the private sector to improve the quality of the internet network in Cibuntu Village.